TRANSFORMATIONAL LEADERSHIP INCREASE SELF FFICACY ON SCHIZOPHRENIC PATIENTS ; A SYSTEMATIC LITERATURE REVIEW - Ashri Maulida Rahmawati; Ifa Nailatul Iza; Zunia Khairunnisa; Budi Istriawan (Universitas Muhammadiyah Kudus, 2024)
Patients with schizophrenia must have good self-efficacy to recover from their illness. Based on previous research, 47% of patients were still at a low level of self-efficacy. Transformational leadership is leadership that allows the leader to move followers to achieve goals directly. This writing aims to describe the influence of transformational leadership by nurses on self-efficacy for recovery in schizophrenia patients. The method of this writing is a systematic literature review. Literature sources research articles and journals with the keywords